Impact of activated carbon on the catabolism of 14C-phenanthrene in soil. Issue 6 (19th May 2015) - Oyelami, Ayodeji O.; Ogbonnaya, Uchenna; Muotoh, Chitom; Semple, Kirk T.
Abstract : Activated carbon amendment to contaminated soil has been proposed as an alternative remediation strategy to the management of persistent organic pollutant in soils and sediments. Abstract : Activated carbon amendment to contaminated soil has been proposed as an alternative remediation strategy to the management of persistent organic pollutant in soils and sediments. The impact of varying concentrations (0%, 0.01%, 0.1% and 1.0%) of different types of AC on the development of phenanthrene catabolism in soil was investigated. Mineralisation of 14 C-phenanthrene was measured using respirometric assays. The increase in concentration of CB4, AQ5000 or CP1 in soil led to an increase in the length of the lag phases. Statistical analyses showed that the addition of increasing concentrations of AC to the soil significantly reduced ( P < 0.05) the extent of 14 C-phenanthrene mineralisation. For example, for CB4-, AQ5000- and CP1-amended soils, the overall extent of 14 C-phenanthrene mineralisation reduced from 43.1% to 3.28%, 36.9% to 0.81% and 39.6% to 0.96%, respectively, after 120 days incubation. This study shows that the properties of AC, such as surface area, pore volume and particle size, are important factors in controlling the kinetics of 14 C-phenanthrene mineralisation in soil.